Relationship between power-duration parameters and mechanical and anthropometric properties of the thigh in elite cyclists - Kordi, M.; Menzies, C.; Simpson, L. P. (European Journal of Applied Physiology, 2018)
Purpose: The curvature constant (W') and asymptote (critical power; CP) of the power-duration relationship are important parameters for explaining cycling performance. Short-duration endurance cycling events rely more heavily on the W'; however, the full mechanistic underpinning of this parameter is yet to be determined. Evidence suggests both muscle volume and muscle strength may contribute to the magnitude of W'. Therefore, the present study investigated the relationship between power-duration parameters (CP and W') and (1) anthropometric and (2) mechanical properties of thigh muscles in a sample of elite cyclists. Methods: Eleven elite male cyclists had gross thigh volume (TVOL), quadriceps muscle volume (QVOL), vastus lateralis (VL) muscle pennation angle (PA) and VL muscle thickness (MT) measured. Additionally, maximum torque production of the knee extensors (FMAX) was assessed. The relationship between these anthropometric and mechanical measures and both the CP and W' were determined. Results: W' showed a very strong positive and significant relationship with FMAX (r = 0.87, p < 0.001) and a large positive and significant relationship with TVOL (r = 0.60, p = 0.05). No other anthropometric characteristics were related to the W'. The CP was not associated with any mechanical or anthropometric parameter. Conclusion: In addition to muscle size, the maximal evocable force of a muscle (group) appears to be linked to the magnitude of the W' in elite cyclists.